Fashion Cycles of Punks and the Mainstream: A US Based Study of Symbols and Silhouettes. (4th May 2021) - Sklar, Monica; Autry, Sharon; Klas, Lauren
Abstract: This research focuses on fashion cycles of punk merchandising interacting with the mainstream. Punks' perceptions of subcultural styles change as the garments move through cycles internal to the scene, and as the looks are disseminated into mainstream society, furthermore as the individuals age. The framework for this study is the entirety of the punk movement in North America: Punks self-identified within the movement without boundaries of time and definition, and therefore the time frame stretches from the 1970s to present day. Data were gathered from self-identified punks in the United States through qualitative mixed methods including an online survey of open ended questions, in-person interviews, archive visits, and social media discussion groups. Findings indicate that over time as the underground punk styles move into mass usage the subcultural silhouettes, or general shape of the garments follow bell curve fashion cycles with little objection from original punk wearers. However, when it comes to punk symbols, such as band logos or iconic in-scene pictorial references, this same progression through fashion cycles tends to be met with resistance from former and current subcultural members. Many punks maintain feelings of attachment to subcultural symbols as they grow older and go through their personal life and stylistic cycles, yet they are more comfortable relinquishing the shapes of subcultural garments to the masses. This research highlights the complications of insular cultures who influence the mainstream and addresses concepts of aesthetics, merchandising, authenticity, and appropriation using punk style as a way to consider design communicating identity and community.